Stress-Strain Relationships of Fiber Reinforced Phosphogypsum under Uniaxial Compression - Li Zhou; Bo Chen; Yong Huang (Advances in Materials Science and Engineering)
To investigate the stress-strain relationship of fiber reinforced phosphogypsum (PG) under uniaxial compression, a total of twenty-seven PG prism specimens were fabricated and tested. The influences of the content of admixture, content of fiber, and water-solid ratio on the stress-strain curve of the specimens were investigated. Three kinds of failure modes were summarized by observing the experimental phenomena; they were called “compaction failure,” “tension failure,” and “mixed stress failure,” respectively. Through in-depth analysis of the test data, it was found that decreasing the water-solid ratio can lead to increasing the peak stress and secant modulus of specimens; increasing the fiber content can lead to improving the mechanical property of PG mixture specimens. However, adjusting the contents of the cement and quicklime has no significant effect on the mechanical property of specimens. In addition, according to the test data and the characteristics of stress-strain curves, the stress-strain curve of PG specimens was divided into four parts, and a mathematical model was developed to predict the stress-strain curve of PG specimens. The validations of the model showed that the curves calculated by the proposed model were well in agreement with the test data of this study and previous studies.